Delivery cost of human papillomavirus vaccination of young adolescent girls in Peru, Uganda and Viet Nam - Carol E Levin; Hoang Van Minh; John Odaga; Swampa Sarit Rout; Diep Nguyen Thi Ngoc; Lysander Menezes; Maria Ana Mendoza Araujo; D Scott LaMontagne (The World Health Organization, 2013)
Abstract Objective To estimate the incremental delivery cost of human papillomavirus (HPV) vaccination of young adolescent girls in Peru, Uganda and Viet Nam. Methods Data were collected from a sample of facilities that participated in five demonstration projects for HPV vaccine delivery: school-based delivery was used in Peru, Uganda and Viet Nam; health-centre-based delivery was also used in Viet Nam; and integrated delivery, which involved existing health services, was also used in Uganda. Microcosting methods were used to guide data collection on the use of resources (i.e. staff, supplies and equipment) and data were obtained from government, demonstration project and health centre administrative records. Delivery costs were expressed in 2009 United States dollars (US$). Exclusively project-related expenses and the cost of the vaccine were excluded. Findings The economic delivery cost per vaccine dose ranged from US$ 1.44 for integrated outreach in Uganda to US$ 3.88 for school-based delivery in Peru. In Viet Nam, the lowest cost per dose was US$ 1.92 for health-centre-based delivery. Cost profiles revealed that, in general, the largest contributing factors were project start-up costs and recurrent personnel costs. The delivery cost of HPV vaccine was higher than published costs for traditional vaccines recommended by the Expanded Programme on Immunization (EPI). Conclusion The cost of delivering HPV vaccine to young adolescent girls in Peru, Uganda and Viet Nam was higher than that for vaccines currently in the EPI schedule. The cost per vaccine dose was lower when delivery was integrated into existing health services.